MODELING AND DESIGN OF OSMOTIC POWER PLANT: AN INVESTIGATION ON OPERATING FACTORS - GOVINDASAMY, MAHA LETCHUMY (Universiti Teknologi PETRONAS, 2021)
Worldwide energy consumption has been profoundly reliant on fossil fuels which cause extreme environmental change therefore the investigation of new technologies to create effective sustainable energy source plays a significant role on the planet. The more the population rise in Malaysia, the more demand for electricity increases. Since fossil fuels are rampantly exploited to depletion in Malaysia, thereby looking into the need for alternative resources is vital. To diminish the dependency on fossil fuel resources, Pressure Retarded Osmosis (PRO) is an encouraging contender by utilising energy from the salinity gradient between fresh water and seawater. According to the economic expansion of membrane technologies and recent improvements in the technology, PRO has possibly sustainable preference and has been actively conducted demonstrations from lab-scale to pilot-scale.